Caenotropus schizodon, a new chilodontid fish from the Rio Tapajós drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae) - Scharcansky, Alexandre; de Lucena, Carlos Alberto Santos (Zootaxa, 2007)
Caenotropus schizodon, n. sp., is described from the Rio Tapajós, Rio Amazonas drainage. The new species is readily distinguished from C. labyrinthicus and C. mestomorgmatos by its bifid premaxillary teeth. Caenotropus schizodon differs from C. maculosus by its lack of teeth on the lower jaw, the dusky distal portions of the anterior dorsal-fin rays but without a distinct patch of dark pigmentation, and the possession of 28-30 lateral-line scales vs. 27 rarely 28. The hypothesis of a sister-species relationship of C. schizodon with C. labyrinthicus is supported by three synapomorphies.